A Guide to Writing in the Sciences - Gilpin, Andrea A., 1969- (Book collections on Project MUSE., 2000)
Written specifically for undergraduate students, this guide describes the basic elements of scientific writing as well as the elements of grammar and punctuation fundamental to all good writing. Clear, concise explanations and examples.